1996
DOI: 10.2118/28586-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Scaleup of Two-Phase Flow in Porous Media Using Phase Permeability Tensors

Abstract: First presented at the SPE Annual Technical Conference & Exhibition held in New Orleans, 25-28 September, 1994, as " Development and Application of a New Two-Phase Scaleup Method Based on Tensor Permeabilities". Abstract The effects of different levels of geological heterogeneity on a fluid displacement process may be captured at a larger scale using scaleup techniques. In the context of reservoir simulation, these are algorithms which should reproduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…Nevertheless, it is usually observed that at relatively small scales capillary forces dominate the displacement process, while viscous and gravitational forces may become more important at larger scales (Odsaeter et al 2015;Kumar and Jerauld 1996;Jonoud and Jackson 2008a). Numerous upscaling methods are available in the literature for two-phase flow (Guzman et al 1999;Jacks et al 1973;Kyte and Berry 1975;Stone 1991;Pickup and Sorbie 1996;Lohne et al 2006;Virnovsky et al 2004;King 1989;King et al 1993;Coll et al 2001;Wallstrom et al 2002;Durlofsky 1997) among which flow-based methods are considered the most reliable. Under this category, two fundamental approaches are employed: steady-state and dynamic pseudos.…”
Section: Importance Of Upscalingmentioning
confidence: 99%
“…Nevertheless, it is usually observed that at relatively small scales capillary forces dominate the displacement process, while viscous and gravitational forces may become more important at larger scales (Odsaeter et al 2015;Kumar and Jerauld 1996;Jonoud and Jackson 2008a). Numerous upscaling methods are available in the literature for two-phase flow (Guzman et al 1999;Jacks et al 1973;Kyte and Berry 1975;Stone 1991;Pickup and Sorbie 1996;Lohne et al 2006;Virnovsky et al 2004;King 1989;King et al 1993;Coll et al 2001;Wallstrom et al 2002;Durlofsky 1997) among which flow-based methods are considered the most reliable. Under this category, two fundamental approaches are employed: steady-state and dynamic pseudos.…”
Section: Importance Of Upscalingmentioning
confidence: 99%
“…Appropriate values for these parameters were calculated using the computer software 'Geopseudo Toolkit' (Ma et al, 2001). This program calculates curves as a function of the absolute permeability using typical Corey type exponent functions of water saturation (e.g., Pickup and Sorbie, 1996). Saturation curves were calculated for different absolute permeabilities and assigned (4), horizontal permeability (k h ) and vertical permeability (k v ) are shown for each zone.…”
Section: Petrophysical and Fluid Propertiesmentioning
confidence: 99%
“…Numerous authors have described steady-state upscaling methods (Lemouzy et al 1993;Pickup and Sorbie 1994;Kumar and Jerauld 1996;Pickup and Carruthers 1996;Pickup and Sorbie 1996;Ekrann and Aasen 2000;Pickup and Stephen 2000;Nomura 2002;Lohne et al 2004) and we provide only a brief overview here. Steady-state upscaling consists of finding the solution of the two-phase immiscible flow equations in the limit of quasi-static variations in fluid saturation with time.…”
Section: Steady-state Upscalingmentioning
confidence: 99%
“…Several studies have used a dimensionless ratio of capillary to viscous pressure drop to determine whether a system is capillary or viscous dominated. Viscous and capillary forces are assumed to act in the same direction within a homogenized averaging volume (Pickup and Sorbie 1994;Zhou et al 1994;Dale et al 1997;Pickup and Stephen 2000;Stephen et al 2001). Yet it is easy to demonstrate that this dimensionless parameter is not sufficient to specify the conditions under which each upscaling method is valid (Jonoud and Jackson 2004).…”
Section: Steady-state Upscalingmentioning
confidence: 99%
See 1 more Smart Citation